(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
The interrelation and mutual influence between digitalization and the social security system are considered one of the essential aspects of modern societal development. The advancement of modern technologies and digital infrastructures is fundamentally transforming social security systems, making them more efficient, rapid, and convenient for citizens. These processes not only improve public service delivery but also contribute to enhancing the quality of services in the field of social protection and expanding their coverage.